ANALYSIS OF FACTORS AFFECTING IN WASTE BANK PROGRAM FOR SUSTAINABLE ENVIRONMENT; A CASE IN MANADO CITY - Warouw, Felly Ferol (Universitas Negeri Manado, 2019)
This research is to conduct an analysis of the management of environmentally friendly waste banks in the city of Manado. The method used is descriptive with a qualitative approach and is limited by three research focuses, namely the first identification of waste management programs in the city of Manado, secondly analyzing community participation in the waste bank development program and identifying factors that are obstacles and supporters in the development of waste banks in the city of Manado. The first research results concerning the identification of waste management there are various programs. For garbage banks to be an alternative solution to the waste problem in Manado City. Secondly, community participation is developing but is still in the consultation stage and not at the community control stage. Participation given by the community in the form of the obligation to sort household waste in the form of organic and inorganic. Third, there are supporting factors in developing a garbage bank in Manado City, namely the role of local and private governments, especially state-owned enterprises, as supporters of the implementation of the garbage bank program. As for the inhibiting factors such as low public awareness, the development of a waste bank requires high investment, low waste value, and the culture of Manado people who view waste as dirty.